1989
DOI: 10.3109/00016358909004798
|View full text |Cite
|
Sign up to set email alerts
|

Differences in functional variables, fillings, and tooth wear in two groups of 19-year-old individuals

Abstract: Fifty-one individuals (28 girls and 23 boys) who had received orthodontic treatment were compared with 47 subjects (19 girls and 28 boys) without such treatment as to maximal mandibular mobility, chewing muscle tenderness, morphologic occlusion, occlusal/incisal state, and degree of tooth wear. All were 19 years old. There were no statistically significant differences between the groups except for the number of teeth present and maximal mouth opening, which were both smallest in those who had received treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Two studies were retrospective analyses reporting on relationships between tooth wear and treatment history. Orthodontic treatment history was not associated with attrition (Dahl et al 1989), whereas extensive restorative treatment and treatments including extraction of teeth seemed to increase the risk for tooth wear (Dettmar & Shaw 1987). No studies were found addressing interventions at certain threshold values of attrition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were retrospective analyses reporting on relationships between tooth wear and treatment history. Orthodontic treatment history was not associated with attrition (Dahl et al 1989), whereas extensive restorative treatment and treatments including extraction of teeth seemed to increase the risk for tooth wear (Dettmar & Shaw 1987). No studies were found addressing interventions at certain threshold values of attrition.…”
Section: Resultsmentioning
confidence: 99%
“…This study (Hachman et al 1999) reported on the effect of a non‐restorative therapy (bite‐plate) to reduce attrition. The two included retrospective studies (Dettmar & Shaw 1987; Dahl et al 1989) cannot be considered intervention studies. They did not compare the true effects of one treatment to another, but merely looked at TSL as a side effect of variable treatments in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of attrition generally relate to changes in the occlusion with age, function, restorations present, bruxism, and 'TMD' (Beyron, 1954;Molnar et al, 1983;Hugoson et al, 1985Hugoson et al, , 1988Dahl et al, 1989;Seligman & Pullinger, 1995). The results of these studies suggest that individuals in general may maintain a low level of wear over their lifetime while others show very high levels very early in life.…”
Section: Risk Assessment Paradigmmentioning
confidence: 99%
“…17 Epidemiological studies of young adults reported that prevalence of tooth wear was in the range 6 to 45%. 18,19 Increased levels of wear in the old age groups are reportedly consistent 20,21 Prevalence of tooth wear of young adults in a United Kingdom study it was reported that a mean proportions of teeth with some moderate wear increased from a few percent to 9% individuals over 65 years of age.…”
mentioning
confidence: 92%